Near field spectroscopy of quantum dots under magnetic field - Zora, A.; Simserides, C.; Triberis, G. (International Journal of Modern Physics B, 2004)
We present the basic steps for the study of the linear near field absorption spectra of semiconductor quantum dots under magnetic field of variable orientation. We show that the application of the magnetic field alone is sufficient to induce -increasing the spot illuminated by the near field probe- interesting features to the absorption spectra.